Structural and Managerial Adjustments Following School Regrouping; Insights from Urban Primary Schools - Napitupulu, Martha; Purba, Jujur; Wiyanti, Dwi; Suwandari, Lilis (Al-Qalam Institue, 2025)
School regrouping has become a strategic policy implemented by the Indonesian government to improve the efficiency and effectiveness of basic education management through institutional mergers. This study explores the impact of school regrouping on institutional governance and operational systems, with a case focus on SDN Pekojan 01 in West Jakarta, which resulted from the merger of SDN Pekojan 01 Pagi and SDN Pekojan 02 Petang. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings highlight substantial changes in leadership structure, teaching and learning organization, resource allocation, and financial management. Regrouping facilitated a unified school identity, improved coordination among stakeholders, and enabled optimal utilization of infrastructure. However, the process also posed challenges such as administrative overlaps, increased workload, and limited supporting facilities. This study emphasizes the importance of strategic planning, adaptive leadership, and inclusive stakeholder involvement in ensuring a smooth transition and maintaining educational quality. The insights provided offer a valuable contribution to the discourse on educational restructuring in urban school settings.